Bacterial Endosymbionts of Bactericera maculipennis and Three Mitochondrial Haplotypes of B. cockerelli (Hemiptera: Psylloidea: Triozidae). Issue 1 (3rd December 2021) - Cooper, W Rodney; Horton, David R; Swisher-Grimm, Kylie; Krey, Karol; Wildung, Mark R
Abstract: Insects harbor bacterial endosymbionts that provide their hosts with nutritional benefit or with protection against natural enemies, plant defenses, insecticides, or abiotic stresses. We used directed sequencing of 16S rDNA to identify and compare endosymbionts of Bactericera maculipennis (Crawford) and the western, central, and northwestern haplotypes of B. cockerelli (Šulc) (Hemiptera: Psylloidea: Triozidae). Both species are native to North America, are known to harbor the plant pathogen 'Candidatus Liberibacter solanacearum' and develop on shared host plants within the Convolvulaceae. The Old-World species Heterotrioza chenopodii (Reuter) (Psylloidea: Triozidae), now found in North America, was included as an outgroup. 16S sequencing confirmed that both Bactericera species harbor 'Candidatus Liberibacter solanacearum' and revealed that both species harbor unique strains of Wolbachia and Sodalis . However, the presence of Wolbachia and Sodalis varied among haplotypes of B. cockerelli . The central and western haplotypes harbored the same strains of Wolbachia, which was confirmed by Sanger sequencing of the wsp and ftsZ genes. Wolbachia was also detected in very low abundance from the northwestern haplotype by high-throughput sequencing of 16S but was not detected from this haplotype by PCR screening. The northwestern and central haplotypes also harbored Sodalis, which was not detected in the western haplotype. Heterotrioza chenopodii harbored an entirely different community of potential endosymbionts compared with the Bactericera spp. that included Rickettsia and an unidentified bacterium in the Enterobacteriaceae. Results of this study provide a foundation for further research on the interactions between psyllids and their bacterial endosymbionts.